Pneumoperitoneum from vaginal cuff dehiscence following blunt trauma in a patient with a history of robotic hysterectomy in Korea: a case report - Byung Hee Kang; Donghwan Choi (Journal of Trauma and Injury)
Pneumoperitoneum usually presents as a surgical emergency, especially in patients with a history of trauma. However, we recently encountered an atypical case of pneumoperitoneum at a hysterectomy site following blunt trauma, indicating that immediate laparotomy may not always be necessary. In this report, we present the case of a 45-year-old woman who was transferred to our trauma center from a local hospital after being involved in a traffic accident the day before. Although she underwent an emergency laparotomy, no bowel perforation was detected. Instead, a rupture was found at the site of a hysterectomy that had been performed 8 months earlier. After repairing the hysterectomy site, the pneumoperitoneum resolved, and the patient was subsequently discharged without further complications.